Assessment of Temporal Effects of Electroporation on CRISPR/Cas-Driven Gene Modifications in Buffalo Embryos - Sardar, Dipankar; Hossain, Md. Taslim; Habib, Adnan (Archives of Veterinary Science, 2025)
Gene editing in buffalo faces challenges from mosaicism, where cells contain both wild-type and mutant alleles, complicating the creation of genetically modified animals in a single step. Traditionally, electroporation is done post in vitro fertilization (IVF) on zygotes, but the higher permeability of mature oocytes suggests earlier intervention could reduce mosaicism and improve editing efficiency. This study aimed to determine if electroporating buffalo oocytes at different stages during in vitro maturation (IVM) could improve biallelic mutation rates for three genes: KDR, GDF9, and POU5F1. Oocytes were electroporated at 44, 46, and 48 hours of IVM, and a control group of zygotes was electroporated 12 hours post-IVF. Each group received three gRNAs targeting the three genes. After electroporation, oocytes were fertilized and cultured to the blastocyst stage. The study assessed and compared blastocyst formation rates, mutation rates, and biallelic mutation occurrences across groups. Electroporation at 44 and 46 hours of IVM reduced blastocyst formation rates but did not significantly impact mutation or biallelic mutation rates compared to the control. Oocytes that were electroporated at 48 hours of IVM showed similar results to those that were electroporated post-IVF. This suggests that the timing of electroporation during IVM affects blastocyst formation but does not influence overall gene editing efficiency, offering a potential method for gene editing in buffalo without the need for IVF.